The importance of the top exporter in regional exports - Francisco Requena Silvente; Juan de Lucio; Raúl Mínguez; Asier Minondo (Investigaciones Regionales - Journal of Regional Research)
We use Spanish firm-level data over the period 1998-2018 to examine the importance of the top exporter in terms of NUTS III (provincial) exports. We find that: (1) the top exporter in each province represents about one fifth of total exports per year; (2) firms contribute to export growth whilst on their way towards the top position but once the latter is reached their growth contribution becomes marginal; and (3), shocks to the top exporter of a province explain the fluctuations in aggregate exports growth.